EROSI DAN TINGKAT BAHAYA EROSI PADA PERTANAMAN KENTANG - Saida Saida; Abdullah Abdullah; Mais Ilsan (AGROTEK: Jurnal Ilmiah Ilmu Pertanian, 2017)
This study aims to predict the erosion and determine the level of hazard of erosion on potato growing, its implementation in the Village Pattapang District of Gowa. The method used for the prediction of erosion is USLE and determination of erosion potential using the approach byt he Department of Forestry. Results obtained by the prediction of erosion on potato crops ranged from 3.34 to 223.11 tonnes /ha/ year and the low level of erosion on SL III 4 and 5, medium level on SLIII2, heavy level on SL III 3, and very heavy level on SL III 1.